2021
DOI: 10.7759/cureus.16839
|View full text |Cite
|
Sign up to set email alerts
|

13q14 Deletion and Its Effect on Prognosis of Chronic Lymphocytic Leukemia

Abstract: Chronic lymphocytic leukemia (CLL) is the most common leukemia affecting adults. CLL results due to uncontrolled accumulation of B lymphocytes in the body with the clinical spectrum ranging from comparatively benign disease to an aggressive form. The disease pathogenesis lies in molecular genetics, the most common alteration being the deletion in the long arm of chromosome 13, at position 14 (13q14) region. This deletion leads to the loss of important microRNAs which are involved in maintaining the critical ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…In this study, Croce et al. evidenced that the 13q14 locus, which is eliminated in many patients with CLL, is actually the site of miR‐15a and miR‐16‐1 [45, 46]. After that, other studies also identified miR‐15a and miR‐16‐1 as tumor suppressors that were deleted or downregulated due to 13q deletion.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…In this study, Croce et al. evidenced that the 13q14 locus, which is eliminated in many patients with CLL, is actually the site of miR‐15a and miR‐16‐1 [45, 46]. After that, other studies also identified miR‐15a and miR‐16‐1 as tumor suppressors that were deleted or downregulated due to 13q deletion.…”
Section: Introductionmentioning
confidence: 76%
“…Furthermore, deletions of 11q, 13q, 17p, 8p, and trisomy 12 are the most common chromosomal abnormalities in CLL [43,44]. For example, cytogenetic studies have shown that 13q deletion is observed in 50% of patients with aggressive and indolent CLL [43,45]. Interestingly, the first attention to the role of miRNAs in cancers began with a study of the 13q14 region in CLL patients.…”
Section: The Correlation Between Mirnas and Cll Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…In Chronic Lymphocytic Leukemia (CLL), the deletion of the 13q14 chromosome segment is the most prevalent chromosomal aberration, affecting 50–60% of patients [ 7 ]. The importance of this deletion is further highlighted by numerous studies focusing on the microRNA miR-15a and miR-16-1 cluster, which is located within the 13q14 region.…”
Section: Discussionmentioning
confidence: 99%
“…An illustrative example of this phenomenon is the Mir-15/16 family of microRNAs. A significant reduction in the expression levels of miR-15a and miR-16-1 due to the deletion of chromosome 13q14, which commonly occurs in chronic lymphocytic leukemia (CLL) patients, was initially observed by Calin et al [ 6 , 7 ]. Significant progress has been made in elucidating the involvement of miR-15/16 in regulating the expression of various genes associated with cell proliferation, apoptosis, and the cell cycle in normal B cells, conferring to them a pivotal role of regulators of the anti-apoptotic B-cell lymphoma 2 (Bcl-2) protein [ 8 ].…”
Section: Introductionmentioning
confidence: 99%